2013
DOI: 10.1088/0957-4484/24/47/475102
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of water-dispersible zinc oxide quantum dots with antibacterial activity and low cytotoxicity for cell labeling

Abstract: Typical photoluminescent semiconductor nanoparticles, called quantum dots (QDs), have potential applications in biological labeling. When used to label stem cells, QDs may impair the differentiation capacity of the stem cells. In this study, we synthesized zinc oxide (ZnO) QDs in methanol with an average size of ∼2 nm. We then employed two different types of polyethylene glycol (PEG) molecules (SH-PEG-NH2 and NH2-PEG-NH2) to conjugate ZnO QDs and made them water-dispersible. Fourier transform infrared spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 52 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…Zinc oxide quantum dots (QDs) with special and strong band gap energy (a mobile charge carrier) as typical photoluminescent (PL) semiconductor NPs have demonstrated antibacterial and anticancer effects. ZnO QDs can be synthesized in liquid media such as alcohol and become water dispersible by conjugation via functionalized groups such as fatty acids, PEG molecules, organosilanes, and polymers (Hsu et al 2013). Previously, our investigations suggested that various ZnO QDs and NPs with modified morphologies have a great antibiotic activity against many dangerous Gram-negative and -positive bacteria (Fakhroueian et al 2013).…”
Section: Introductionmentioning
confidence: 89%
“…Zinc oxide quantum dots (QDs) with special and strong band gap energy (a mobile charge carrier) as typical photoluminescent (PL) semiconductor NPs have demonstrated antibacterial and anticancer effects. ZnO QDs can be synthesized in liquid media such as alcohol and become water dispersible by conjugation via functionalized groups such as fatty acids, PEG molecules, organosilanes, and polymers (Hsu et al 2013). Previously, our investigations suggested that various ZnO QDs and NPs with modified morphologies have a great antibiotic activity against many dangerous Gram-negative and -positive bacteria (Fakhroueian et al 2013).…”
Section: Introductionmentioning
confidence: 89%
“…Among different processing methods, the sol–gel technique has various advantages such as cost-efficient processing, low-temperature sintering capability, the possibility of coating large and complex surfaces, and the capability to produce high quality coatings with a wide range of easily controlled thicknesses [5]. Preparation of ZnO nanoparticles by a colloidal method in the form of hydrosols was widely investigated in recent years in connection with a possible employment in biology [6]. ZnO nanoparticles have been synthesized in conjunction with different polymers such as polyethylene glycol (PEG) and poly( N -vinylpyrrolidone) (PVP).…”
Section: Introductionmentioning
confidence: 99%
“…Although QDs have been utilised for stem cell tracking and imaging for many years [51][52][53][54][55][56][57][58], most toxicity and pharmacokinetic studies have focused on the behaviours of II B-VI A and III A-V A QDs in rodents [59]. Investigations of the IV A QDs are still in the early stages.…”
Section: Quantum Dotsmentioning
confidence: 99%